2012
DOI: 10.2141/jpsa.011053
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Germline Chimeric Chickens Using Primordial Germ Cells

Abstract: Chicken primordial germ cells (PGCs) are used to restore and conserve genetic resources of some endangered birds or flocks of domestic chickens. When PGCs are transferred from a donor to a recipient, they can survive and gain sexual maturity in the recipient chicken. This indicates that PGCs retaining exogenous genes can proliferate and develop in recipient gonads, and proves that transferred PGCs are effective sources for establishing transgenic and germline chimeric chickens. The PGC transfer method has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Qian et al (2010) reported that PGCs was formed out of gonad and migrated toward gonad during embryogenesis which will be developed into spermatozoa and ovum. Primordial germ cells might be used as genetic source and for establishing transgenic chicken (Furuta 2012). Primordial germ cells were cells with plurypotent characteristic making the PGCs as a good model to study embryonic development by in-vitro (Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al (2010) reported that PGCs was formed out of gonad and migrated toward gonad during embryogenesis which will be developed into spermatozoa and ovum. Primordial germ cells might be used as genetic source and for establishing transgenic chicken (Furuta 2012). Primordial germ cells were cells with plurypotent characteristic making the PGCs as a good model to study embryonic development by in-vitro (Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pembentukan ayam germline chimera mempunyai arti penting untuk penelitian fisiologi, tingkah laku dan biologi perkembangan. Germline chimera mempunyai aplikasi yang sangat potensial untuk generasi unggas transgenik, untuk konservasi spesies yang terancam punah dan untuk melakukan perubahan seks rasio pada industri unggas pedaging (Ishiguro et al 2008;Kang et al 2008;Furuta 2012). Germline chimera mempunyai aplikasi praktis di dalam konservasi spesies dan stok genetik yang ada, karena dapat memelihara material genetik dengan cara menyimpan PGCs yang dibekukan dibandingkan dengan memelihara hewan hidup (Mozdziak et al 2006).…”
Section: Gambar 3 Morfologi Pgcs Setelah Kriopreservasiunclassified
“…Numerous studies had reported the isolation and collection of PGCs from gonadal embryos (Nakamura et al, 2011;Nakajima et al, 2011;Nakajima et al, 2016). Moreover, germline chimeras had been produced in chicken by transferring PGCs or GGCs into the bloodstream at 2-day-old recipient embryos (Furuta et al, 2007(Furuta et al, , 2008 so that PGCs could be used as a genetic resource to produce germ line chimera (Furuta, 2012). Nakajima et al (2012) reported that gonadal PGCs collected from 7-day-old chick embryos and incubated in PBS [-] can be used to produce germline chimeras.…”
Section: Introductionmentioning
confidence: 99%